Pengaruh Komunikasi Interpersonal dan Kompetensi Terhadap Prestasi Kerja Pegawai Dinas Pertanian Kota Bogor - ., Halimah; Djamil, Masyhudzulhak; Pasaribu, Popy Novita (Jurnal Manajemen, 2015)
Work performance was the result of achievement by an employee at any given time. Many factors that affect job performance an employee, including interpersonal communication and compentence. The purpose of this study was to determine and analyze the influence of interpersonal communication and competence towords job performance at the Department of Agriculture Bogor City. This research method included in the survey with of associative methods. The population in this study were all civil servants in the city of Bogor Agricultural Department with the number 64 people. The data collection was done by spreading the questionnaire to the respondents, the data were analyzed with quantitative approach in the form of multiple linear regression, t test and F test. Based on the results of the study was found 1) interpersonal communication significantly influence employee job performance with the sig. 0.049 <? 0.05. This means that Ho was rejected and Ha accepted at 95% confidence level. 2) Competence significant effeceted on employee job performance with the sig. 0.000 <? 0.05. Wich meant Ho was rejected and Ha accepted at 95% confidence level. 3) Interpersonal Communication and competence had a significant effect jointly on job performance at the Bogor Agricultural Department with sig value. 0.000 <?0, 05. Finally, the authors suggested to the Head of Department of Agriculture Bogor City in order to provide direction to staff to be able to create effective interpersonal communication, and proceeded in a two-way or reciprocal, and with good competence of the employees w0uld be able to do the tasks to which it aspires was optimal, so that the turn would improve their work in the future.